2003
DOI: 10.1097/00045415-200301000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Focal Parvovirus B19 Myocarditis in a Patient with Brugada Syndrome

Abstract: The Brugada syndrome is characterized by a distinct ECG pattern consisting of ST segment elevation in the right precordial leads and right bundle branch block, a propensity for life-threatening arrhythmias, and an apparently structurally normal heart. The authors describe the case of a patient with an aborted sudden cardiac death and the typical ECG signs of Brugada syndrome. Nevertheless, magnetic resonance imaging displayed signal enhancement in the left ventricular myocardium. Additionally, histologic exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The knowledge that myocarditis may mimic the BS is not novel 22 ; nevertheless, the present study indicates that it can be recognized in as much as 77% of an unselected population that presents with the clinical phenotype of BS and sustained The major reduction in current density obtained with the R367H mutation did not allow further characterization of current kinetics.…”
Section: Endomyocardial Biopsy Findings In Patients With Bs and No Scmentioning
confidence: 56%
“…The knowledge that myocarditis may mimic the BS is not novel 22 ; nevertheless, the present study indicates that it can be recognized in as much as 77% of an unselected population that presents with the clinical phenotype of BS and sustained The major reduction in current density obtained with the R367H mutation did not allow further characterization of current kinetics.…”
Section: Endomyocardial Biopsy Findings In Patients With Bs and No Scmentioning
confidence: 56%
“…B19V infection, detected most often by serological evidence of recent infection and sometimes by the detection of viral genomes in cardiac tissue, has been reported in myocarditis in the fetus (see the section on hydrops below), in infancy, during childhood, and among young adults (174,176,(832)(833)(834)(835)(836)(837)(838)(839)(840). In one center's series of 19 pediatric patients, the presenting symptoms were upper respiratory and gastrointestinal symptoms; all infected children had ventricular dysfunction, 2 died, and 3 required heart transplantation (176).…”
Section: Clinical Manifestations Diseases Caused By B19v Infectionmentioning
confidence: 99%
“…reported the case of a 34-year-old patient with resuscitated sudden death due to documented acute myocarditis and an ECG suggesting Brugada syndrome [3]. Likewise, Frustaci et al found pathological findings consistent with myocarditis in more than 75% of a cohort of patients with symptomatic Brugada syndrome [4].…”
mentioning
confidence: 98%
“…Echocardiographic assessment of acute hemodynamic response during optimization of resynchronization pace-maker using different pacing modalities and atrioventricular delays☆ In patients with the manifested heart insufficiency and bundle branch block with prolonged duration of QRS complex, cardiac resynchronization therapy (CRT) with its dyssynchrony reduction leads to symptom reduction, life quality improvement and better prognosis [1][2][3]. However in some number of patients this therapy does not improve symptoms and signs of the disease [4,5].…”
mentioning
confidence: 99%